Pitting corrosion failure analysis of a wet gas pipeline. (December 2017) - Mansoori, Hamed; Mirzaee, Reza; Esmaeilzadeh, Feridun; Vojood, Arash; Dowrani, Alireza Soltan
Abstract: This paper presents corrosion failure analysis of an underground natural gas pipeline. The pipeline material grade is API 5L X65 with 10-in ID. The pipeline transfers multiphase fluid (gas, condensate, and water) from a gas well to a gas gathering plant, located 4200 m away from the well site. A portion of the line failed due to pitting corrosion under unknown circumstances. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) are employed to characterize the scales and/or corrosion products near the failed portion. Based on visual and microscopic analyses and reviewing the background information, the following pitting corrosion sequences were identified: the oversized pipeline changed the dominant flow regime to "stratified". In the stratified flow regime, the accompanying water phase accumulated in the pipelines' low points. Considerable concentration of calcium ions along with high pH in CO2 media favored precipitation of calcium carbonate. The relatively thick scales adhered to the pipe surface were partially loosened and removed by the regional turbulent flow. This exposed the fresh steel surface to the corrosive media. The uncovered areas acted as the preferential anodic sites coupled with nearby large cathodic sites which were covered by scales and/or corrosion products. Under such conditions, pits emerged on the steel surface until one of them grew faster and failed the gas pipeline. Highlights: CO2 pitting corrosion failure of a multiphase gas pipeline is analyzed. Partial removal of precipitated surface layers resulted in generation of active-passive corrosion cells on the pipe wall. Corrosion inhibitors could not prevent pitting corrosion while metal surface is unclean. Multiphase behavior of wet gas pipeline greatly influenced CO2 pitting corrosion rate.